DO JIGSAW WITH AND WITHOUT EDMODO NEEDED IN TEACH INTEGRATED SKILLS (Reading and Writing)? - Farida Salim (Graduate Program, University of Islam Malang, 2021)
To get good writing skills requires a lot of practice, as well as in the process of producing a paragraph which also requires structured stages. In supporting the writing process, appropriate teaching and learning methods need to assist students master writing skill. In his study, researcher offers alternative methods to measure the effectiveness of writing narrative text using the Jigsaw method with Edmodo and conventional Jigsaw. Its research design was quasi-experimental with a non- randomized, pre-post test design. The study was conducted at X Grade Multimedia (MM 1 and MM 2) students of SMK PGRI 2 Kediri in the academic year 2019/2020, consist of 20 students each class. The writer uses the writing test as an instrument in collecting data; and with pre-post test design form. The test used to classify students’ writing ability in relation to the effect of the treatment. Then, an analytic scoring rubric used by two raters worked independently in scoring the students’ writing. The results showed that the mean scores of the three writing components in the experimental group were not significantly different or nearly the same. This is shown by statistical calculations using the Independent Sample of T-test with a significant value at the level of 0.145> 0.05. These findings indicate that there is no significant difference between students' scores in learning using Jigsaw with Edmodo and conventional Jigsaw. There was an increase in student scores, but the increase was not too significant. These findings suggest that there is insufficient evidence to reject the null hypothesis. Then the alternative hypothesis is not accepted. Students taught using Jigsaw with Edmodo did not have a significant difference in learning achievement and writing narrative text compared to students who were taught using conventional Jigsaw. Based on the research finding, the students taught using Jigsaw with Edmodo do not get a significantly better score in writing narrative text than students taught using Jigsaw conventional. Even though, there is no significant level student score improvement the application jigsaw with Edmodo and Conventional Jigsaw was suggested to English teachers to apply those methods to improve students’ writing skill. The students will be nice when using a media likes Jigsaw and Edmodo in the teaching-learning process. For future research, writer recommend to fill the gaps of this research limitation as a reference in conducting research both in the same or different field. Keywords: Jigsaw, Edmodo, Writing, Narrative Text To get good writing skills requires a lot of practice, as well as in the process of producing a paragraph which also requires structured stages. In supporting the writing process, appropriate teaching and learning methods need to assist students master writing skill. In his study, researcher offers alternative methods to measure the effectiveness of writing narrative text using the Jigsaw method with Edmodo and conventional Jigsaw. Its research design was quasi-experimental with a non- randomized, pre-posttest design. The study was conducted at X Grade Multimedia (MM 1 and MM 2) students of SMK PGRI 2 Kediri in the academic year 2019/2020, consist of 20 students each class. The writer uses the writing test as an instrument in collecting data; and with pre-posttest design form. The test used to classify students’ writing ability in relation to the effect of the treatment. Then, an analytic scoring rubric used by two raters worked independently in scoring the students’ writing. The results showed that the mean scores of the three writing components in the experimental group were not significantly different or nearly the same. This is shown by statistical calculations using the Independent Sample of T-test with a significant value at the level of 0.145> 0.05. These findings indicate that there is no significant difference between students' scores in learning using Jigsaw with Edmodo and conventional Jigsaw. There was an increase in student scores, but the increase was not too significant. These findings suggest that there is insufficient evidence to reject the null hypothesis. Then the alternative hypothesis is not accepted. Students taught using Jigsaw with Edmodo did not have a significant difference in learning achievement and writing narrative text compared to students who were taught using conventional Jigsaw. Based on the research finding, the students taught using Jigsaw with Edmodo do not get a significantly better score in writing narrative text than students taught using Jigsaw conventional. Even though, there is no significant level student score improvement the application jigsaw with Edmodo and Conventional Jigsaw was suggested to English teachers to apply those methods to improve students’ writing skill. The students will be nice when using a media likes Jigsaw and Edmodo in the teaching-learning process. For future research, writer recommend to fill the gaps of this research limitation as a reference in conducting research both in the same or different field. Keywords: Jigsaw, Edmodo, Writing, Narrative Text